Damage of tubule cells in diabetic nephropathy type 2: Urinary N-acetyl-β-D-glucosaminidasis and γ-glutamil-transferasis - Vlatković Vlastimir; Stojimirović Biljana; Obrenović Radmila (Vojnosanitetski Pregled)
Background/Aim. A damage of tubular epithelial cells is followed by the release of cell enzymes and production of proinflammatory compounds, which lead to the tubulointerstitial damage. The aim of this study was to examine the function of renal tubules in the patients with diabetes mellitus type 2 (DM type 2) and the various proteinuria degrees, to establish the damage of the proximal tubule cells caused by DM type 2 by determining urinary N-acetyl-β-D-glucosaminidasis (β-NAG) and γ- glutamil-transferasis (γ-GT) activity in urine, as well as to compare the obtained results in the examined groups of patients with the values in the healthy examinees. Methods. A complete examination of renal function and selective enzymuria was performed in 37 patients with DM type 2, and 14 healthy examinees as the controls. The patients were divided in three groups according to the degree of proteinuria. The first group consisted of the patients with diabetes without microalbuminuria; the second one consisted of the patients with proteinuria of < 300 mg/24 h, and microalbuminuria of >20 mg/24 h, while the third one included the patients with proteinuria of >300 mg/24 h. Results. In the patients with DM type 2 and the preserved global renal function, fractional excretion of sodium, potassium and phosphates, as well as renal threshold of phosphates concentration, were not sensitive parameters for discovering the damage of the renal tubule function. The determination of β-NAG activity proved to be the most sensitive parameter for early discovering of tubule cells damages. The difference among the examined groups was statistically highly significant. Conclusion. The increased presence of β-NAG in the urine of DM type 2 patients, pointed out an early tubular disorder and damage of cells, while γ-GT was a less sensitive indicator of this damage.